Influence of educational actions on transitioning of food safety culture in a food service context: Part 2 - Effectiveness of educational actions in a longitudinal study. (February 2021) - Zanin, Laís Mariano; Stedefeldt, Elke; da Silva, Sueli Maria; da Cunha, Diogo Thimoteo; Luning, Pieternel A.
Abstract: Recently, the food safety culture (FS-culture) gained attention as a critical factor for reducing foodborne diseases. This study investigated the effectiveness of educational actions in the transition of FS-culture in a longitudinal study using action research in an army food service, which was selected as a case. We hypothesised that the FS-culture assessment might be a good starting point to develop educational actions. First, we identified the educational needs of food handlers and managers based on a FS-culture assessment, followed by the implementation of educational actions using three formats (tutored, planned, and with the managers). A previously developed mixed-method approach was used for the collection of qualitative and quantitative data, data triangulation, and an interpretation grid that was used for categorisation into reactive, active, or proactive FS-culture. The triangulated data showed that the prevailing FS-culture changed from reactive to more proactive during the longitudinal study. The educational actions changed attitudes, practices, personal relationships, and the work environment. The educational actions were effective in influencing the prevailing FS-culture and confirmed the research hypothesis. Furthermore, the mixed-method approach with the interpretation grid was useful in assessing the transition in the prevailing FS-culture. Further research may test the usefulness of other types of food services in other countries. We also recommend converting the scientific methods for FS-culture assessment into methods suitable for the use by food safety managers in food services. Highlights: FS-culture assessment may be used as a starting point for educational actions. Educational actions evolved the prevailing FS-culture proactively. Action research built confidence, which was indispensable to evolve FS-culture. Educational actions changed personal relationships and team interaction. The changes in the degree of risk seem to impact the risk perception longitudinally.